A Longitudinal Study of Korean Marriage Culture - Buja, Elena (Amsterdam University Press, 2022)
This small-scale study aims to trace the changes that have occurred in the Korean marriage culture in a time span of about one hundred years, more specifically, since the beginning of the 20th century, when Korea opened its borders to foreigners, until the present, as well as to identify the causes that have led to these changes. The theoretical framework I employed is content analysis, whereas the content (data) subjected to analysis is represented by fragments excerpted from a number of novels authored by Korean and Korean-American writers, which are categorized according to their themes and coded in terms of non-verbal elements. The focus is on such nonverbal codes as rituals, exchange of artifacts, eligible age for marriage, as well as on the status roles created by marriage in the Korean culture. The primary data is supplemented with information coming from the Korean society trend survey, conducted by Statistics Korea. The findings of the analysis reveal a slow, though obvious change in the marriage traditions that can be related to Western influence, the spread of Christianity, as well as to the massive industrial, technological, and economic development of Korea.
Keywords: (South) Korea; East Asia; Heritage and Culture; Marriage; Non-verbal elements; Status roles